1994
DOI: 10.1093/nar/22.24.5425
|View full text |Cite
|
Sign up to set email alerts
|

An AP1 binding site upstream of the kappa immunoglobulin intron enhancer binds inducible factors and contributes to expression

Abstract: Expression of the kappa immunoglobulin light chain gene requires developmental- and tissue-specific regulation by trans-acting factors which interact with two distinct enhancer elements. A new protein-DNA interaction has been identified upstream of the intron enhancer, within the matrix-associated region of the J-C intron. The binding activity is greatly inducible in pre-B cells by bacterial lipopolysaccharide and interleukin-1 but specific complexes are found at all stages of B cell development tested. The fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 26 publications
1
16
0
Order By: Relevance
“…To explore the potential role of Net-b in B-cell development, we studied the pre-B cell line, 70Z/3, which can be induced to differentiate with LPS. LPS is known to stimulate SRE activity (24), Fos-Jun DNA binding activity (43), and p38 MAP kinase (16,17). We found that LPS induction of 70Z/3 pre-B-cell differentiation increases TC-forming activity to a small extent.…”
Section: Discussionmentioning
confidence: 99%
“…To explore the potential role of Net-b in B-cell development, we studied the pre-B cell line, 70Z/3, which can be induced to differentiate with LPS. LPS is known to stimulate SRE activity (24), Fos-Jun DNA binding activity (43), and p38 MAP kinase (16,17). We found that LPS induction of 70Z/3 pre-B-cell differentiation increases TC-forming activity to a small extent.…”
Section: Discussionmentioning
confidence: 99%
“…The human Igκ gene contains an NF-κB site and a perfect consensus AP-1 site within the iEκ and the downstream iEκ. In B lymphocytes, both enhancers can be activated by nuclear factor NF-κB and AP-1 at different degrees (41,42).…”
Section: Some Regulatory Mechanisms Of Ig Expressed In Cancer Cellsmentioning
confidence: 99%
“…7], immunoglobulins (e.g., light chain; ref. 8), inflammatory enzymes (e.g., COX-2; ref. 9), and matrix metalloproteinases (e.g., MMP-13; ref.…”
mentioning
confidence: 99%